Ecological Characteristics of Aphidophagous Menochilus Sexmaculatus Fabricius and its Performance Against Aphis Gossypii Glover - Adisubroto, Fransiscus Xaverius Wagiman (1996)
The chilli aphid, Aphis gossypii Glover (Homoptera: Aphididae) (here after abbreviated as AG), is vector of the chilli veinal mottle virus (CVMV) and is a main pest of chilli in Malaysia. The aphidophagous Menochilus sexmaculatus Fabricius (Coleoptera: Coccinellidae) (here after abbreviated as MS) is a well known predator of the aphid and hereby its ecological characteristics and predatory performance were assessed. In nature, MS maintains its population on aphids of com, beans, sambau weed and other plants. The predator searched its prey in random manner and tended to aggregate in high prey density. Both prey and predator were distributed in a clumped pattern. Larval and adult MS showed no preference for any prey stages and prey species. However, there was a weak preference for AG over Aphis craccivora Koch.